(untitled) - WIDYANINGRUM, AYU (Language Horizon: Journal of Language Studies, 2014)
Ivan’s Self-deception and Hypocrisy in Leo Tolstoy’s The Death of Ivan Ilych Ayu Widyaningrum English Literature Faculty of Languages and Arts State University of Surabaya Ayu_widya75@yahoo.com Drs. Much. Khoiri, M.Si. English Department Faculty of Languages and Arts State University of Surabaya Much_choiri@yahoo.com Abstrak Penelitian ini focus pada penggambaran penipuan diri yang dilakukan oleh tokoh utama dalam novel The Death of Ivan Ilych oleh Leo Tolstoy dan bagaimana penipuan diri tersebut memunculkan kemunafikan. Penipuan diri terjadi sebagai hasil dari ketidaksiapannya dalam menerima kenyataan bahwa dia sedang menghadapi kematian. Untuk menjawab permasalahan pertama, penelitian ini menggunakan teori penipuan diri oleh Annette Barnes yang didukung oleh beberapa filsuf dan dengan tanda-tanda orang yang menipu dirinya sendiri oleh James Peterman. Permasalahan kedua dijawab dengan menggunakan konsep kemunafikan. Data dalam penelitian ini menyajikan tentang penipuan diri yang dilakukan oleh Ivan dan bagaimana penipuan diri tersebut memunculkan kemunafikan dalam dirinya. Analisis dalam penelitian ini mengungkapkan penipuan diri yang dilakukan oleh Ivan dan tanda-tanda bagaimana dia menjadi seseorang yang menipu dirinya sendiri. Penipuan diri ini digunakan untuk mengurangi kecemasannya terhadap ketidaksiapannya dalam menghadapi kematian. Selain itu, penipuan diri ini muncul sebagai hasil dari kecemasannya tentang keinginan hidup yang tidak terpenuhi karena sakit yang dialami. Selanjutnya, penipuan diri yang dialami memunculkan kemunafikan dalam dirinya. Ivan mengalami tiga macam kemunafikan, kemunafikan kepura-puraan , kemunafikan menyalahkan , kemunafikan inkonsistensi. Perilaku kemunafikan tersebut bersumber dari sikap penipuan diri. Kata Kunci : Penipuan Diri, kemunafikan, kecemasan, kematian Abstract This study focuses on depicting self-deception performed by the main character and how his self-deception gives raise to his hypocrisy. The self-deception is used as the result of his unreadiness in accepting the truth that he faces death. To answer the first problem, this study uses the theory of self-deception by Annette Barnes and supported by several philosophers and the symptoms of Self-Deception offered by James Peterman. The second problem is answered by using the concept of hypocrisy. The data presents Ivan Ilych’s self-deception and how his self-deception gives raise to his hypocrisy. The analysis reveals Ivan’s self-deception and the symptoms how he becomes a self-deceiver. The self-deception is used to reduce his anxiety toward his unreadiness in facing his death. Besides, his self-deception emerges as the result of his anxiety about the desire of life which is unfulfilled because of the illness. Furthermore, his self-deception gives raise to his hypocrisy. Ivan experiences three kinds of hypocrisy, they are hypocrisy of pretense, hypocrisy of blame, hypocrisy of inconsistency. Those hypocritical behaviors are rooted by his self-deception. Keywords: self-deception, hypocrisy, anxiety, death INTRODUCTION Novel is literary work which presents more detail and complicated problems. The readers will get more experience, fantasy and imagination by reading it. A great novel is born from a great writer. With a lot of great novels in the world, automatically there are also many great writers whether they are from west or east part of the world. There are many problems and phenomenon that is existed by the writers in their literary works, such as culture and tradition, sociological and psychological problem, and so on. There are many writers exist the psychological problems which is related to the personality of the characters in their literary works. It can be seen in Russian writers. There are so many literary works from Russia and their several novels state about psychological problem that is related with the personality of the characters. One of the great famous Russian writer is Leo Tolstoy. Leo Tolstoy, the author who was born in Yasnaya Polyana, Russian Empire in 1916. There were many literary works which were made by this Russian writer, such as short stories, poems, plays, essays. Some of his works are war and peace and Anna Karenina are acknowledge as two of the greatest novels of all time and pinnacle of realist fiction. His novels are so well planned, written, and executed that Tolstoy’s finished story is a perfectly formed narrative. And, critics agree that his work alone defines the true nature of an epic novel that eerily depicts the joys and sorrows of real life. Tolstoy is equally known for his complicated and paradoxical persona and for his extreme moralistic and ascetic views, which he adopted after a moral crisis and spiritual awakening in the 1870s, after which he also became noted as a moral thinker and social reformer. During the 1860s, and encouraged by his publisher, Tolstoy wrote War and Peace. During this time, he also endeavored to write a novel about Peter I the Great and about educational pedagogy, but thereafter finished what would become the greatest book of his time. Following, Tolstoy released Ana Karenina, which was considered as important as War and Peace, but with a slightly different focus – ethics and virtues can evolve and change over time. Unhappy with the Russian Orthodox Church and its teachings, which he found blasphemous, Tolstoy started his own church based on five tenets. For this, he was excommunicated, but gained his own followers, who were more like cult members than clergymen. These five tenets inspired Gandhi in his passive approach to violence – evil cannot be combated with evil. His novella, entitled The Death of Ivan Ilyich is often regarded as one of the best short novels ever written. The Death of Ivan Ilych, first published in 1886, is considered as one of the masterpieces of his late fiction, written shortly after his religious conversation of late 1870s. The Death of Ivan Ilych is deeply religious work, but religious of its own terms. The protagonist is a somewhat clueless, spiritually empty hero whose long illness forces him to confront the meanings of both death and life. Ivan Ilych represents a small but important class of urban bureaucrats, prominent in the day-to-day running of Russian affairs in Tolstoy’s days, whose live became increasingly detached from nature, the land, and spiritual values. By exposing the horrible vacuity of Ivan Ilych’s life, Tolstoy explores the self-deception, immorality and alienation of a whole class of individuals. Although Ivan is nowhere near as intelligent as his creator, like Tolstoy he comes to accept death and gain deep, if painful understanding of what his life has meant. The novel embodies the kinds of values and purpose Tolstoy thought literature should have. The Death of Ivan Ilych conveys the existential horror of sickness and morality while describing civilization as a web of lies designed to distract people from an awareness of death and also it is perfectly demonstrates this introspection as it magnifies a man’s struggle with how to live his life. There are considerations of taking the novella as the main source of analysis. The first is novella performs the characteristics of self-deception and hypocrisy which experiences by the main character of the novel. The second reason is that in Leo Tolstoy’s The Death of Ivan Ilych, he set out merely to describe a single segment of society or to present a single example of humanity and also his writing is very honest. Besides, the story uses words which are easier to understand. The last consideration can be the best reason why this novella is analyzed by using theory of self-deception. In The Death of Ivan Ilych also has conflict and problem, both external conflict and internal conflict. Ivan is everyman an average nineteenth century bureaucratic functionary, a bourgeois, a middle class citizen (Sklare, 1965 : 3). The Death of Ivan Ilych is about an ordinary man, has a bright childhood and good life. His pleasure of life changed, since his marriage brings him unpleasantness and incurable illness that tortures him biological and psychologically until he dies. The illness makes him to stay in bed day and night with a great pain, worse than biological pain, psychologically it tortures him by the horror of death. Not believing that he will die, he struggle to avoid death by deceives his own self that he is not dying and hides his real condition by being hypocrite to his environment, but his efforts are useless. Having fought against death, ultimately he realizes that he is mortal. At the end, he accepts it and dies in piece. Death is such a taboo subject to discuss in our society, but actually it is human nature. What Woody Allen writes may be able to explain how allergic people are to death. “I am not afraid of dying, but I just don’t want to be there when it happens” (Coon, 1992 : 436-437). Psychology finds that people do not like to talk about death because they are afraid of it. The pool to 1500 adults shows that there are no fears of death ; yet. They find another possibility. It may be more exact to say that the people hide and intense denial to death (Coon, 1992 : 436). The fact that all men must die is hardly news, and as an abstract statement it dulls our fears at least as much as it aroused them. The Death of Ivan Ilych is one of interest novella by Leo Tolstoy that can be analyzed because it tells about psychological sides of human’s life that lead to the main point self-deception and hypocrisy of the main character named Ivan Ilych. Having the feeling of anxious in facing death makes people tend to do something which can reduce his anxiety. People tend to deceive himself by believing that he is not facing death and forces to think that his condition is better while he knows well that he suffers illness which leads him to the death. The topic in this thesis is about self-deception and hypocrisy, because it is the most important one and it is suffered by the main character, Ivan. Self-deception is a mental defense mechanism by which some people cope with intensely painful emotions. They avoid becoming aware of, or accepting the truth about, a current life circumstance or person simply because it is too painful or scary to do so (from http://nirmukta.com/2010/06/21/self-deception-as-a-coping-mechanism-among-victims-of-the-sai-baba-cult/). Meanwhile, there is also another term that almost has the same meaning as self-deception which is hypocrisy. Based on the online dictionary, hypocrisy is “the condition of a person pretending to be something he is not, especially in the area of morals or religion; a false presentation of belief or feeling. The study of self-deception and hypocrisy are related to the main character in Leo Tolstoy’s The Death of Ivan Ilych. In this novella Ivan as the main character of the story experiences self-deception. He forces himself to believe something which he knows that it is false. It happens when he faces illness that leads him to the death. He knows well that the illness will leads him to the death, but he keeps forcing himself to think that everything will fine even his life will not be disturbed by the illness. Ivan is someone who has ambitious in life. He desires that his life should be easy, pleasant and decorous. When he gets the illness, he feels fear that it will give big impact in his life. He feels anxiety that his desires about life will not fulfill because of that illness. That is why he uses self-deception to reduce his anxiety. Meanwhile there is also another term that almost has the same meaning as self-deception is hypocrisy. Self-deception is so related to hypocrisy. It is because self-deception is the root of hypocrisy. If someone experiences hypocrisy in his life, it can be analyzed that he also experiences self-deception as the root of his hypocritical behavior. Furthermore, if someone experiences self-deception in his life, it might also lead him to have hypocritical behavior. The main character Ivan experiences self-deception in his life, and his self-deception give raise to his hypocritical behavior. He pretends that he is fine, hides his real condition even though in the depth of his heart he knows that his illness is getting worse and will lead him to the death. In addition, this novel ever discussed about the anxiety by Anita Christina HR from English Literature 2004 entitled Ivan’s Enxiety in Leo Tolstoy’s The Death of Ivan Ilych. It tells about the anxiety experienced by the main character Ivan in this novel. This study will not same with that previous study, because this study will discuss about self-deception in the main character Ivan, and how Ivan’s self-deception give raise to his hypocrisy. The idea to unearth the self-deception and hypocrisy of the main character probably is not the main message of the novel, but the freedom of reader’s interpretation lets unguessed ideas be out of the author’s purpose, even exceed the consciousness of the author. These all ground the creating this thesis with potential title “Ivan’s Self-deception and Hypocrisy in Leo Tolstoy’s The Death of Ivan Ilych”. RESEARCH METHOD The used method is descriptive quality; it means the quality of the data becomes the reference to work rather than the quantity of the data. Besides, a technique is needed to understand the data. Technique of interpretation must be used to interpret and analyze the data. Through interpretation the analysis can be worked. Interpretation is a crucial step that has to do before analyzing the data. Then, extrinsic approach is used as an approach toward the analysis in which environment belongs to it. According to method above, the first thing that has to do is collecting data. In collecting data this research focuses on reading and documentation. Reading novel. In this step, novel becomes the object of the research. The novel is entitled The Death of Ivan Ilych, written by Leo Tolstoy. To collect the correctly data, it needs reading more than once, because to get interpretation, it needs understanding all contents completely with all possibilities both intrinsically and extrinsically. Inventorying data. This step is collecting data through noting the quotations related to the statement of the problems and objectives of the study, it is including in words, sentences, and discourse that can represent self-deception and hypocrisy in Leo Tolstoy’s The Death of Ivan Ilych. Thus, all data that will be analyzed are started and sourced through the novel’s contents. Classification data. It is appropriate to the statements of the problems about self-deception and hypocrisy in Leo Tolstoy’s The Death of Ivan Ilych. Tabling the data. It is to simplify reading the data and classify data that is used in the analysis for the readers. Continuously, the selected data or the collected data, which are related to the statements of the problems and the objectives, are analyzed through self-deception and hypocrisy to the main characters in Leo Tolstoy’s The Death of Ivan Ilych. SELF-DECEPTION Barnes argues that in self-deception, self-deceivers must intentionally get themselves to believe something they know or truly believe is false (Barnes, 1997 : 4). It means that self-deception only involves one person, she/he is not only as deceiver but also deceived. It is the difference between interpersonal deception and self-deception, that in interpersonal deception, one intentionally gets the other one to believe something, but in self-deception, deceivers intentionally get themselves to believe something. The same thing is also confirmed by Mele in his book Irrationality. The conception of self-deception as lying to oneself is fueled by the idea that interpersonal deception necessarily involves lying to another. If deceiving someone else is getting him to believe something that one knows (or correctly believes) is false, it is natural to understand self-deception as getting oneself to believe something that one knows (or correctly believes) is false. (Mele, 1987 : 122). Deceiving someone else is to make the other person believe something that the deceiver knows it is false. While in self-deception, deceivers make themselves to believe something which they know it is false. Self-deception involves just one person, where she or he is not only become deceiver but also deceived. In self-deception, deceivers must intentionally get themselves to believe something which they know or truly believe is false. I deceived myself, then (Barnes, 1997 : 18) : (a) As deceiver, I must believe of some proposition that it is false, and at the same time, as deceived, believe that it is true, and (b) As deceived, I must be taken in by a deceitful strategy that, as deceiver, I know to be deceitful As quoted by Mele, according to Demos self-deception exists when a person lies to himself, that is to say, persuades himself to believe what he knows is not so. In short, self-deception entails that B believes both p and not-p at the same time. (Mele, 1987 : 122). It means that in self-deception, deceivers know what they believe is actually false, but they keep believing something false in themselves. . That is called as self-deceivers believes both p and not-p. they know the truth, but still keep believing the false. Self-deceptive belief functions to reduce anxiety. The self-deceptive belief that p may function to reduce anxiety that not-p, it can sometimes function instead to reduce anxiety about some other proposition (Barnes, 1997 : 36). This suggests that when self-deceivers deceive themselves into believing that some future event will occurs, their self-deceptive beliefs function to reduce their anxiety about the non-occurrence of that event. Self-deceptive belief always functions to reduce a self-deceiver’s anxiety, whether the self-deceptive belief is about what will occur, what has occurred, or what is occurring. A belief that p functions to reduce anxiety that not-q when (Barnes, 1997 : 59) : (1) the belief that p is caused by the anxious desire that q and (2) the purpose of the occurrence of the belief that p is to reduce anxiety that not-q According to requirement 1, the anxious desire plays a casual role in the person’s coming to have that belief. According requirement 2, the having of the belief that p is purposive. Its purpose is to reduce anxiety that not-q. Barnes argues that self-deceiver’s anxious desires cause them to be biased in favor of beliefs that reduce their anxiety (Barnes, 1997: 59). People have self-deceptive beliefs because having self-deceptive beliefs reduces their anxiety. Something (having a self-deceptive belief) which has a certain effect (reducing anxiety) is explained by the fact that it has that effect (Barnes, 1997 : 60). HYPOCRISY People do something because they have a motive. Everything which is done by them is a sign of their motive or the aim they have. When they want to get attention from others, they tend to do something which can make the other people give them attention. It can be done by the people who did not intend to deceive. They do something which is consistent with their motive. Deceit is done by the signs of outward deeds. Such as when a person pretends to have a good purpose or intent through their actions, but in reality it was a bad goal. The purpose is actually bad and not in accordance with the action they did. It can be said as a lie. The lie can be regarded as hypocrisy. A deed is a sign of the person’s intention. But it is not so for the hypocrite, who by outward signs of deeds or things signifies that which he is not (Spiegel, 1999 : 20) As quoted by Spiegel, philosopher Gilbert Ryle suggests that to be hypocritical is to try to appear actuated by a motive other than one’s real motive (Spiegel, 1999 : 23). A hypocrite takes an action to deliver a purpose that is not the real goal. They tend to hide the real goal with actions which they are doing. So it conveys through his actions, others will accept that the goal is not their real goal. They made ??their actions as a mask to hide the true purpose. Hypocrisy is an act to make a 'belief', in which he pretended to believe what he actually knows that's not the real problem/case. These actions will continue to do so leads to a different motive other than the actual motive. The hypocrite engages in action which, as it were, contradict or “negate” one another morally. One is morally good, while the other is bad. Thus, the hypocrite is irrational, because inconsistent, in the moral sense (Spiegel, 1999 : 30). Hypocrisy hates the truth. Because a hypocrite’s self-worth is based on maintaining an illusion of righteousness and godliness to himself and the others, he must continually deceive himself and others that his righteousness is genuine. However, since his righteousness is not genuine, he must be on constant guard against fact, circumstances, or people that might expose him. Instead of the truth being the foundation of his life, values, and hope, it becomes an enemy against which he must always be on guard (Matthew 6:23 ; Luke 11:34-36 ; john 3:19-21) ( http://questions.org/attq/whats-so-dangerous-about-hypocrisy/ ) Others will be difficult to understand what he was hiding. It is because the hypocrite will continue to provide the signs, through actions to cover up the truth. Not only through actions, hypocrites with their self-consciously deceive others through his language, the words they said to others. Those are why the lie will be difficult to be understood. KINDS OF HYPOCRISY Roger Crisp and Christopher Cowton offers a fourfold distinction of the vice, which are (Spiegel, 1999 : 30) : Hypocrisy of Pretense The hypocrisy of pretense occurs when a person puts up a front of being morality or physically better than he is. Pretentious hypocrites are motivated by desire for selfish gain. But as Crisp and Cowton note, pretenses may be motivated by malice, shame, and even interest in others (Spiegel, 1999 : 30). Nor must the pretense aim to sham genuine virtue. People experiences hypocrisy of pretense when they hide their real motive which is better rather that the real motive. For instance, a person is feeling in bad condition but when the other people ask about his condition he tends to hide by telling that his condition is good. This example can indicate that this person is experiencing hypocrisy of pretense. Hypocrisy of Blame Hypocrisy of blame, defined as moral criticism of others by someone with moral fault of their own. The vice often appears to lie particularly in the fact that the fault of the critic is worse than criticized (Spiegel, 1999 : 31). Hypocrisy of the blame Occurs when the perpetrator has an error then he tends to put the blame on to someone else. it is done with the purpose to cover up his own mistakes. By blaming others actually he does not realize that his sin was far worse than the mistake he accuses. It was because he had an error and then add the mistake of accusing others with the intent to cover up his mistake which ended up being worse. Hypocrisy of Inconsistency The third category of hypocrisy is that inconsistency, which is defined as the uttering of some (overriding) moral requirement that does apply to oneself and then failing to live up to it. Hypocrisy of inconsistency occurs when a person’s action is not in accordance to his words. For instance, a person told to his friend that he would read a novel but then the other friend of this person sees that he is not reading a novel but he is playing piano. The other example which can be indication of hypocrisy of inconsistency is when a person promised to himself or another person about something, but in fact he does not do what has been said by his own self. Judith Sklar regards it as “the distance between assertion and performance” (Spiegel, 1999 : 31). Hypocrite are generally regarded as insincere the faults of the other two characters are quite different. The hypocrite engages in action which, as it were, contradict or “negate” one another morally. One is morally good, while the other is bad. Thus, the hypocrite is irrational, because inconsistent, in the moral sense. Hypocrisy of complacency Lastly, complacency in certain conditions can be said a form of hypocrisy. To be guilty of this is to ignore the demands of morality when they become costly, to be content with one’s moral status, refusing to improve or even to reflect upon it, while carrying on a pretense of virtue blaming others for they vices, or failing to practice what one preaches. Thus, as Crisp and Cowton note, complacent hypocrites protect “their complacency from criticism on the grounds of the first three kinds of hypocrisy” (Crisp and Cowton, 1994: 343-345). The hypocrisy of complacency could also fall into any of these categories, as suggested by Crisp and Cowton’s own assertion that such hypocrites may sustain their complacency through any of the other forms of hypocrisy ; pretense, blame or inconsistency (Spiegel, 1999 : 32). RELATIONSHIP BETWEEN SELF-DECEPTION AND HYPOCRISY Some writers maintain that at least in some form, hypocrisy is rooted in self-deceit. The self-deceived which can be called as ‘internal’ hypocrite is characterized by psyche fractured by refusal to fully own up to some moral truth she knows in her heart to heart (Spiegel, 1999: 33) . The self-deceived person tends to act that way because of she/he wants to refuse some moral truth she/he knows. It can be caused by her/his unreadiness of accepting the truth. The self-deceived person tends to ‘make believe’ in which he/she pretends to believe what she/he knows that it is not the case. The delusional person experiences no conflict in her belief of a lie, for she is completely convinced. On the other hand, the self-deceived does experiences conflict because of her belief contradicts her knowledge. Self-deceived actually knows that what she/he has done contradicts to her knowledge. Hypocrisy involves self-deception when it results from either: (1) A false belief resulting from a motivated bias of some sort, (2) A disavowal of some continuing engagement in which one is involved, or (3) Some combination of 1 and 2. Some writers prefer to see hypocrisy as a “second order” or “meta” vice. It means that self-deception occurs as the result of self-deception that happened before. In the words of Crisp and Cowton, it is symptomatic of “a failure to take morality seriously” (Spiegel, 1999 : 35). It can be said that it is metavirtuous to acknowledge the domain of morality, that is, to be moralist. But the hypocrite is metavicious, for someone tacitly refuses to do so, and is therefore an amoralist such a person considers herself somehow exempt from moral constraints. And yet, being aware of how the moral community operates and when and why rewards are doled out to the virtuous, the hypocrite plays a part for personal gain. As quoted by Spiegel, Christine McKinnon notes that hypocrite “wishes a certain status and she recognizes that this can be achieved if she can manage the elicit positive moral assessments” (Spiegel, 1999 : 35). So like the self-deceived hypocrite, the amoralist hypocrite gains praise and respect for qualities she does not really possess. But unlike the self-deceived hypocrite, she experiences no psychological dissonance, because she is genuinely convinced that she is not the subject to the relevant moral rules. As quoted by Szabados and Solfer, Shklar argues that allowing self-deception to count would result in a regrettable proliferation of accusations of hypocrisy (Solfer, 2004 : 256). It is possible that such hypocrisy involves, not only deception to others, but rather than self-deception, which may not similarly involve knowledge that one is engaged in deception. In short, self-deception and hypocrisy are two terms which cannot be separated because they have relationship each other. Self-deception can also be called as internal hypocrisy, a hypocrisy which is done to his/her own self. A deceived and a deceiver are the same person. Meanwhile hypocrisy can also be called as interpersonal deception, a deception which is done to the other people. Hypocrisy involves more than two people, there is a deceiver and also involves the other people which become deceived. Besides, self-deception can give raise to hypocrisy when a person becomes self-deceiver, there is a possibility that makes him/her becomes hypocrite. It is because self-deception is the cause of hypocritical behavior. One and the same hypocrite’s actions are as resulting from self-deceit or lack of moral seriousness. Self-deceit and amoralism as dual causes of hypocritical behavior (Spiegel, 1999 : 36). If self-deception is deceiving their own selves to believe something they know that it is false. If the self-deceptive belief results action, behaviour, language or something else which lead them to deceive others rather than their own selves, it can be said that their self-deception give raise to their hypocrisy. Thus we can see how self-deception and hypocrisy have relationship each other and cannot be separated. DEPICTION OF IVAN’S SELF-DECEPTION Self-deception is a mental defense mechanism by which some people cope with intensely painful emotions. The self-deceivers are becoming aware of, or accepting the truth about, a current life circumstance or person simply because it is too painful or scary to do so. In this novel, the central drama of the story is Ivan's struggle with illness and death, and Tolstoy gives us quite the setup. He tells us Ivan's whole life story up to the point when he becomes sick. We get to know Ivan, his habits and desires, his family and friends, and his circumstances. The main character Ivan is someone who experiences self-deception because he is not ready in accepting the truth that he is facing illness which leads him to the death Ivan forces himself thinking that he is getting better. He keeps forcing himself to believe that the illness is getting better and the medicine begins to take the effect. But then the usual pain is coming back to him, he becomes more painful because the illness feels more serious. As he grows sicker, Ivan's mood and attitude toward life begin to change dramatically. He starts having to struggle with fear, discomfort, and isolation. The illness begins after he slipped when he was preparing his new house. Ivan feels everything is well after his move to his new house, but sometimes Ivan complains of a strange taste in his mouth and something wrong with his left side, but this could hardly be called as an illness. The something wrong grows worse, and although it is not real pain, it is a feeling of pressure in his side which throws him into a constant state of depression. The state of depression depends and begins to spoil the pleasure of the easy and decorous life that the Golovin family had recaptured. As his ill humor begins to mar the easy and agreeable lifestyle he has worked so hard to construct, volatile disputes with his wife occur more and more often. Ivan goes to see the doctor. To him, the only important question is whether his case is serious or not. But ignoring Ivan's concern, the doctor focuses on the strictly medical question of whether Ivan's problem is a floating kidney or appendicitis. This question the doctor answers brilliantly, and as Ivan thought, in favor of the appendix. Ivan gets the feeling that his case is very serious and he is struck by the doctor's indifference and utter lack of sympathy to a matter of such importance. After think about his illness, he becomes more realize that he is going closer to the death. It shows that Ivan reviews from the beginning when the first time he gets the pain from his illness. It begins when he slipped in his new house, then he get a bruise which hurts a little. But then it becomes more painful, so he visit to the doctor to consul about the pain he feels. He is not sure to the doctor’s diagnosis then he intents to see another doctor to get more accurate diagnosis. But from the other doctors, he gets the same diagnoses which resume that his illness is chronic. Then from doctor’s resume, he gets the thought that it is not the case of what disease he is suffering, but it is about life and death. Demos argues that self-deception exists when a person lies to himself, that is to say, persuades himself to believe what he knows is not so, self-deception entails that someone believes both p and not-p at the same time (Mele, 1987 : 122). This argument also confirms what is being experienced by Ivan, because based on quotations in the novel it is clear that he believes something contradictory at the same time. On the one hand he fully understands that there is something bad in him as a result of his illness, he knew it was the explanation from the doctors he visited. On the other hand, he forced himself to think that there would be no bad thing in him, and believe that it is not a chronic disease, unlike what has been described by doctors. Then it can clearly be seen that in this case Ivan lies to himself. Barnes argues that a belief that p functions to reduce anxiety that not-q when (1) the belief that p is caused by the anxious desire that q (Barnes, 1997 : 59). In Ivan’s case, a belief about his illness that it is just a small thing functions to reduce his anxiety that it is a chronic illness not a small thing as he believes. It occurs because his belief is caused by his anxious desire that it is a chronic disease. Ivan has anxious feeling about his illness, he will not it becomes chronic because it will make him die. In the depth of his heart, he feels so anxious with what has been said by the doctor, he knows well that the doctor diagnoses there are something bad in himself because of his illness. He also feels that his condition becomes worse gradually, and becomes more understand about the illness from medical book he read. All these things make his anxious feeling becomes worse. That is why he always forces himself to think that he is getting better and his illness is just small thing, it functions to reduce his anxious feeling. It occurs when the purpose of the occurrence of the belief that p is to reduce anxiety that not-q (2) (Barnes, 1997 : 59). Barnes explain that the belief about p does not only function to reduce anxious feeling but also has the purpose to reduce it. Ivan’s belief about his illness does not only function to reduce his anxious feeling, it also has a purpose. His purpose to have a belief that his illness is just a small thing is to reduce his anxious feeling that it is a chronic disease. Ivan feels anxious that his illness will mar his pleasure of life. Ivan is someone who has desire in life that his life ought to be easy, pleasant, and decorous. He has bright childhood, good life, and good physic, mental and social background. . He is someone who has big ambitious in life, especially in his job. He will do everything to fulfill his pleasure of life. In his mind, the happy frame of life comes from his success in job and the harmonious relation with his wife, the one augmenting the other. Everything goes in accordance with what he desires in his life. But since he married with Praskovya Fredorovna, his easy, pleasant and decorous of life changes gradually. He feels that his marriage cannot bring him the pleasant of life. He realizes that being married at least to this wife, does not necessarily augment the pleasures and proprieties of life, but on the contrary, threatened them and that therefore he must guard himself against these threats. Something worse happens and then begins to mar his easy, pleasant and decorous life. He suffers the chronic illness which makes his condition became worse gradually. Since he got an incurable illness that has tortured him biologically and psychologically, Ivan feels anxious. He feels anxious because he seems that he is not ready in facing death and also he feels anxious that his illness will mar his easy, pleasant and decorous life. As the time goes by, and the illness becomes worse more than before, automatically Ivan cannot live his life like he used to live, easy, pleasant and decorous. Peterman describes in the symptoms of self-deceiver that A part of the explanation for A’s believing that P is that A desires that P (Spiegel, 1999 : 56). If it is used to analyze Ivan’s case, the A stands for Ivan as the self-deceiver and P is Ivan’s belief that his illness is just a small thing. Ivan believes it because he desires it to be. Ivan believes that his illness is just a small thing that it is actually not a chronic diseases because he indeed desires everything is well. Then his desires lead him to keep believing that his illness is just nothing, just a small thing. he does not want his illness will destroy what he has believed about his life that it should be run in accordance with what he believed : easy, pleasant and decorous. REVEALATION OF IVAN’S SELF-DECEPTION GIVES RAISE TO HIS HIS HYPOCRISY There is also another term that almost has the same meaning as self-deception which is hypocrisy. Based on the online dictionary, hypocrisy is “the condition of a person pretending to be something he is not, especially in the area of morals or religion; a false presentation of belief or feeling” (http://www.thefreedictionary.com/hypocrisy). Indeed, hypocrisy is very close to self-deception but it may affect one else rather that just between his/ her own self. Self-deception and hypocrisy are two terms which are cannot be separated. It is because at least in some forms, hypocrisy is rooted in self-deceit. Self-deception is also called as internal hypocrisy. Self-deception is deceiving themselves to believe something they know that it is false (Spiegel, 1999 : 33). If the self-deceptive belief results action, behavior, language or something else which lead them to deceive others rather than their own selves, it can be said that their self-deception give raise to their hypocrisy. It has been analyzed that Ivan experiences self-deception in his life, but unfortunately his self-deception give raise to his hypocrisy. Ivan does not only deceive himself in the matter of facing his illness. His self-deceptive belief results action, language and behavior which lead him to deceive others rather than his own self. Ivan’s self-deception give raise three kinds of hypocrisy, they are hypocrisy of pretense, hypocrisy of blame, and hypocrisy of inconsistency. HYPOCRISY OF PRETENSE Ivan experiences hypocrisy of pretense in himself. It happened when he had to struggle with the illness. As explained in the previous analysis of self-deception, he has a belief in himself that his illness is just a small thing. Ivan believes that his illness is just a small thing, that it is actually not a chronic disease. It is because he indeed desires everything is well. Then his desires lead him to keep believing that his illness is just nothing, just a small thing. he does not want his illness will destroy what he has believed about his life that it should be run in accordance with what he believed : easy, pleasant and decorous. He realizes that his illness will destroy his faith about life. Then he forces himself to think that he is getting better. But then it appears the internal conflict in his heart, because his belief contradicts with the fact that his illness is a chronic disease. He knows that he is dying, but he is unable to grasp the full implications of his mortality. He sees that he is dying, and he is in a constant state of despair. In his heart of hearts he knows he is dying, and it is not simply that he could not get used the idea that he could not grasp it, could not possibly grasp it. He hides his real condition by pretending though his words that “the appendix is getting better”. But then the painful feeling of his illness follows his words. By doing so, everyone especially his wife in this case, will consider that indeed he is in a good condition because he say to her that “the appendix is getting better”. It occurs to a hypocrites, they will act through their action and language by their self-conciously that this action or this utterance is false. It is done to hide the actual case. That occurred in Ivan’s case, when his friend and his wife or everyone in his environment considers that Ivan illness is just a small thing, Ivan success becoming hypocrite. A hypocrite takes an action to deliver a purpose that is not the real goal. They tend to hide the real goal with actions which they are doing. So it conveys through his actions, others will accept that the goal is not their real goal. They made their action as a mask to hide the true purpose (Spiegel, 1999 :20). From the quotation above, Ivan uses “cheerfully” action as a mask to hide his condition, so it leads the other goal which is his wife will assume that his condition is good. It is called that Ivan’s pretense will raise another perception in his wife’s perspective, rather than the actual case that Ivan never forget about the pain which is caused by his illness. He pretends and hides his real condition to everyone, so then it leads the thought of everyone that Ivan is in a good condition. Everyone think that Ivan is just suffers simply disease, not a chronic disease. The only thing that Ivan need is simply following the doctor’s treatment and taking his medicine regularly. By doing so, Ivan will get better again as he used to be before he got the illness. Others will be difficult to understand what he was hiding. It is because the hypocrite will continue to provide the signs, through actions to cover up the truth (Spiegel, 1999 : 23). The quotation above shows that how everyone does not know about the real condition of Ivan. It is because Ivan always hides it by acting like he is not suffering the chronic illness. HYPOCRISY OF BLAME Ivan’s self-deception give raise to his hypocrisy of pretense because in the matter of hiding his condition, Ivan does not only experience hypocrisy of pretense, but also hypocrisy of blame. When everything goes but it is not in accordance with what he wants, he blames his wife. He also blames his wife’s attitude that it seems like his wife does not notice him. Ivan’s attitude in hiding his condition causes his wife’s attitude towards his illness. Ivan thinks that his wife seems not notice and will not understand about his condition. It is described clearly by the statement above, that his wife’s attitude is actually his own fault. But Ivan seems that he is blaming his wife because of her attitude. In this case, his wife’s attitude toward him happens as a result of his own deception. As it has been described in the previous analysis about hypocrisy of pretense, that Ivan hides his real condition by pretending through his “cheerful” action, then it leads to his wife’s perspective, she assumes that indeed Ivan is in good condition. By thinking that way, automatically she also will not too worry with his condition. So then his attitude in blaming his wife can be called as his hypocrisy of blame, which is rooted by his own deception. Ivan hides the doctor’s diagnose about his illness from everyone even his wife. Ivan seems blame everyone’s attitude toward him that they seem annoyed and do not want understand about his condition. He does not realize that the environment’s attitude toward his illness is a result of his hypocritical behavior which he pretends as he is not suffering chronic disease. Then it automatically leads the thought that he is indeed in a good condition, so then everyone will notice him like a person who is in good condition and will not give more attention like the attention to person who is suffering chronic disease. Ivan hates his wife who is actually always giving him attention but he himself always rejects it. The only one to blame is actually Ivan himself, it was because he pretends and hides the actual condition. The second is because he always refused any attention that is given by his wife. When someone is always giving attention, but the attention she gives was rejected then she will feel bored to continue giving attention to the same person. Likewise with Ivan’s wife, who wants to give him more attention even by every simple way, but Ivan always refused and thought that his wife would not understand his real condition. Actually it is Ivan’s mistake because he does not want show the doctor’s diagnosis to everyone, including his wife. When his wife tries to ask about the doctor’s diagnosis he lies and hides it by telling that everything is fine. With all his mistakes, he blames his wife. He does not realize that actually the only one to blame is his own self which is cause by his own behavior, not the mistakes of other people even his wife. Finding Ivan's condition even worse, however, his wife chooses to tell Ivan to take his medicine rather than make the announcement. Ivan looks at his wife with extreme animosity and tells her to let him die in peace. Ivan greets the doctor with the same hostility, declaring that the doctor can do nothing for him. The doctor admits to his wife that Ivan's case is very serious, and that he can only administer drugs to ease the pain. Yet more than his physical sufferings, Ivan's mental sufferings cause him the greatest torture. One night Ivan begins to doubt whether he has lived his life correctly. It occurs to him that his official life, the arrangement of his family, and all his social interests are actually false. He wants to defend his life path, but finds that there is nothing to defend. Realizing that the only truth in his life was when he attempted to struggle against the expectations and values of high society, Ivan realizes that his life "was not real at all, but a terrible and huge deception which had hidden both life and death." Seeing the footman, his wife, his daughter, and all the other people he comes across in his daily routine confirms to Ivan the truth of his realization. This consciousness increases his suffering "tenfold." For the first time, Ivan recognizes the hypocrisy and artificiality of his life. He calls into question the values that he has lived by, and he honestly entertains the conclusion that the way he lived has obscured both life and death. A proper view of life, Ivan now understands, entails an acknowledgment of the inevitability of death, as well as an appreciation of the true joys of life. The two go hand in hand. By accepting unpleasantness as a fact of life, one can derive full benefit from life's joys. Ivan's realization has affected a shift in the focal point and intensity of his spiritual suffering. Ivan no longer feels obliged to take part in the pretense around him. He confronts both his wife and the doctor with the truth of his condition. Now, however, Ivan's spiritual pain is caused by the possibility that his whole life has been in error. Yet despite Ivan's new knowledge, Ivan still does not wholly relinquish the hope that his life was lived rightly. Even though he is now keenly aware of the spiritual component of life, he is not yet ready to fully admit the error of his life. In a sense, he knows it, but does not acknowledge it. In this manner, Tolstoy paves the way for the resolution of the life and death of Ivan Ilych. HYPOCRISY OF INCONSISTENCY Ivan's attempts to deal with the disruption caused by his illness are also revealing. By following the doctor's orders in a scrupulous and exact fashion, he not only takes up the position that his illness is purely physiological, but he also demonstrates his belief that life is well regulated and predictable. With his wife's pregnancy, Ivan managed to adopt a perspective that ignored the disagreeable aspects of her behavior. And when the proper channels of complaint failed to gain Ivan notice when he was passed over for promotion, a sudden and miraculous reorganization of the government landed him a better position. Yet unlike the previous incursions of unseemliness and unpredictability into his life, Ivan's illness resists such decorum restoring measures. When meticulous attention to the doctor's instructions fails to help, Ivan tries to force himself to think that he is better. But even self-deception is unsuccessful when problems with his wife, difficulty at work, or bad cards at bridge make him conscious of his disease. The fact that life's unpleasantness causes the pain that Ivan experiences is a key to Ivan's condition. If Ivan's condition is not physiological, but is truly caused by a misperception of the nature of life, i.e., if Ivan's illness stems from his belief that life is always proper, formal, decorous, and neat, then any signs to the contrary would serve to aggravate his symptoms. A close look at Ivan's night of bridge seems to point to the same conclusion. Ivan enjoys bridge because it mirrors his perception of reality. Bridge, in a sense, is a metaphor for Ivan's ideal of a proper life. Thus, when Ivan realizes that his excitement at making a grand slam (the best possible bridge hand) is ridiculous in light of his present condition, bridge seems to lose all its appeal. Ivan's illness makes him conscious of the fact that bridge does not reflect the true nature of life. Missing a grand slam, as Ivan does when he misplays his hand, is really a trivial occurrence. Ivan simply does not care. And the reason that "it is dreadful to realize" why he does not care is because that realization implies the destruction of his worldview. Although Ivan has not yet completely relinquished his view of life as neat and predictable, his illness is gradually making him aware that a world and a reality exist outside of the one he occupies. He begins to deal with himself that he should stop being too aware of his condition as the impact of his illness, the only thing he should do is just going to one doctor and follow the instruction in order to get better. Ivan believes and hopes when he follows the instruction and takes the medicine regularly, his condition will get better. But then his wife tells to the doctor how Ivan does not follow the doctor’s instruction by not taking his medicine. Then it clearly described that Ivan becomes inconsistence, because his action is not accordance with what has been said by him. Two more weeks pass by, and Ivan's physiological condition degenerates further. One morning Praskovya enters Ivan's room to tell him that their daughter's suitor has formally proposed. Finding Ivan's condition even worse, however, she chooses to tell Ivan to take his medicine rather than make the announcement. Ivan looks at his wife with extreme animosity and tells her to let him die in peace. Ivan does not want follow his wife’s demand, he did not take the medicine even his condition has become more serious and worse. Ivan greets the doctor with the same hostility, declaring that the doctor can do nothing for him. The doctor admits to Praskovya that Ivan's case is very serious, and that he can only administer drugs to ease the pain. His wife tells that Ivan does not take the medicine and does not follow the doctor’s instruction. The only thing he does is just lying in his bed while his legs up, because he feels better by doing so. Ivan does not consistence with what he has been told and promised that in the previous he said that he will follow the doctor’s instruction and take his medicine regularly, but in fact he does not do it. It indicates that what Ivan is not in accordance with what he has told that it can be said as hypocrisy of inconsistency. As Judith Sklar regards about hypocrisy of inconsistency is that “the distance between assertion and performance” (Spiegel, 1999 : 31). Where it can be described that what happen to Ivan is hypocrisy of inconsistency, does as Ivan said, not as Ivan does. CONCLUSION Based on the whole analysis of the study in chapter 3, there are several conclusions in line with the statement of the problem. Based on the definition of self-deception which has been explained by Barnes that self-deception involves just one person, that person does not only become deceiver but also deceived. The deceivers are getting themselves to believe something that they know or truly believe is false. It occurs to the main character Ivan in The Death of Ivan Ilych. The central drama of the story is Ivan's struggle with illness and death, and Tolstoy gives us quite the setup. He tells us Ivan's whole life story up to the point when he becomes sick. The writer gets to know Ivan, his habits and desires, his family and friends, and his circumstances. Ivan experiences self-deception in his life as a result of his unreadiness in accepting the truth that he is facing death. Barnes argues that the self-deceptive belief functions to reduce anxiety. It also occurs to Ivan that he feels afraid in facing his illness. He seems aware even anxious that the illness will disturb his pleasure of life. That is why he uses self-deception to reduce his anxiety about not fulfilling of his pleasure of life and the anxious because of his unreadiness in facing death. Furthermore, Ivan’s self-deception gives rise to his hypocrisy. Self-deception is deceiving themselves to believe something they know it is false, if this self-deceptive believe result action, language, behaviour or something else which lead them to deceive others rather than their own selves, it can be said that his self-deception give raise to his hypocrisy. In Ivan’s case, his self-deception results action, language, behaviour and something else which lead him to deceive others rather than his own self. So it can be analyzed that Ivan’s self-deception gives rise to his hypocrisy. Ivan’s self-deception gives rise to three kinds of his hypocritical behaviours those are hypocrisy of pretense, hypocrisy of blame and hypocrisy of inconsistency. His hypocrisy of pretense appears to hide his real condition from people around him. Besides hypocrisy of pretense, Ivan’s self-deception also gives raise to his hypocrisy of blame. Ivan blames his environment’s attitude toward his condition that they tend does not pay more attention to his condition. Actually it is his own mistake that he hides his real condition which leads the attitude of everyone that they will not give him more attention. Ivan blames the other person which actually the only person to blame is his own self. Lastly, Ivan also experiences hypocrisy of inconsistency. It occurs because he does not take his medicine regularly. Whereas he has promised that he will allow the doctor’s instruction by taking his medicine and does not eat food which is forbidden by the doctor. It indicates that what Ivan does is not in accordance with what he has said. All hypocritical behaviours performed by Ivan are rooted by his self-deception. Basically self-deception is root of hypocrisy. When someone experiences self-deception, she/he has possibility to be hypocrite. But in the end story of Ivan, Ivan realizes that he has actually been traveling opposite his intended direction. Moving up in social esteem has not led to joy, fulfillment and life, but to misery, emptiness and death. Blinded by the values of high society, he has been traveling in the wrong direction on the road of life. After Ivan's climactic realization, his waking life is defined by one thing, suffering, and lots of it. But he has at least finally stumbled on the thing he needs to recognize: his life was wrong. when Ivan realizes his error and comes to a fuller understanding of the nature of life, he is reborn spiritually and experiences extreme joy. REFERENCES Barnes, Annette. 1997. Seeing Through Self-Deception. Cambridge : Cambridge University Press. Coon, Dennis. 1992. Introduction to Psychology : Exploration and application (6th Edition). St Paul : West Publishing Company. Jabrohim. 2001. Metodologi Penelitian Sastra. Yogyakarta : PT hanindita Graha Widia. Mele, Alfred R. 1987. Irrationality. Oxford : Oxford University Press. Sklare, Arnold B. 1965. The Art of the Novella. New York : The Macmillan Company. Solfer, Bela Szabados & Edon. 2004. Hypocrisy : Ethical Investigation. Canada : Broadview press, Ltd. Spiegel, James S. 1999. Hypocrisy : Moral Fraud and Other Vices. United States of America : Baker Books. Tolstoy, leo. 1960. The Death of Ivan Ilych and Other Stories. London : The New American library of World Literature, Inc. Waluyo, Herman. 2002. Apresiasi dan Pengajaran Sastra. Surakarta : Sebelas Maret University Press. Wellek, Rene & Austin Warren. 1949. Theory of Literature. New York: Harcourt, Brace and Company.